Wayanin and guaijaverin, two active metabolites found in a Psidium acutangulum Mart. ex DC (syn. P. persoonii McVaugh) (Myrtaceae) antimalarial decoction from the Wayana Amerindians. (1st July 2016) - Houël, Emeline; Nardella, Flore; Jullian, Valérie; Valentin, Alexis; Vonthron-Sénécheau, Catherine; Villa, Pascal; Obrecht, Adeline; Kaiser, Marcel; Bourreau, Eliane; Odonne, Guillaume; Fleury, Marie; Bourdy, Geneviève; et al.
Abstract: Ethnopharmacological relevance: Psidium acutangulum Mart. ex DC is a small tree used by the Wayana Amerindians from the Upper-Maroni in French Guiana for the treatment of malaria. Aim of the study: In a previous study, we highlighted the in vitro antiplasmodial, antioxidant and anti-inflammatory potential of the traditional decoction of P. acutangulum aerial parts. Our goal was then to investigate on the origin of the biological activity of the traditional remedy, and eventually characterize active constituents. Materials and methods: Liquid-liquid extractions were performed on the decoction, and the antiplasmodial activity evaluated against chloroquine-resistant FcB1 ([ 3 H]-hypoxanthine bioassay) and 7G8 (pLDH bioassay) P. falciparum strains, and on a chloroquine sensitive NF54 ([ 3 H]-hypoxanthine bioassay) P. falciparum strain. The ethyl acetate fraction (D) was active and underwent bioguided fractionation. All the isolated compounds were tested on P. falciparum FcB1 strain. In vitro anti-inflammatory activity (IL-1β, IL-6, IL-8, TNFα) of the ethyl acetate fraction and of an anti- Plasmodium active compound, was concurrently assessed on LPS-stimulated human PBMC and NO secretion inhibition was measured on LPS stimulated RAW murine macrophages. Cytotoxicity of the fractions and pure compounds was measured on VERO cells, L6 mammalian cells, PBMCs, and RAW cells. Results: Fractionation of the ethyl acetate soluble fraction (IC50 ranging from 3.4 to <1 µg/mL depending on the parasite strain) led to the isolation of six pure compounds: catechin and five glycosylated quercetin derivatives. These compounds have never been isolated from this plant species. Two of these compounds (wayanin and guaijaverin) were found to be moderately active against P. falciparum FcB1 in vitro (IC50 5.5 and 6.9 µM respectively). We proposed the name wayanin during public meetings organized in June 2015 in the Upper-Maroni villages, in homage to the medicinal knowledge of the Wayana population. At 50 µg/mL, the ethyl acetate fraction (D) significantly inhibited IL-1β secretion (−46%) and NO production (−21%), as previously observed for the decoction. The effects of D and guiajaverin (4 ) on the secretion of other cytokines or NO production were not significant. Conclusions: The confirmed antiplasmodial activity of the ethyl acetate soluble fraction of the decoction and of the isolated compounds support the previous results obtained on the P. acutangulum decoction. The antiplasmodial activity might be due to a mixture of moderately active non-toxic flavonoids. The anti-inflammatory activities were less marked for ethyl acetate fraction (D) than for the decoction. Graphical abstract: